Strategi Guru PAI Dalam Mengatasi Perilaku Bullying - Mufidah, Vika Nurul; Fadilah, Nadiah Nurli; Huda, Muhammad Nurul; Yasik, Fatkhu; Herlambang, Unu Putra (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2024)
This study aims to analyse the strategies implemented by Islamic Education (PAI) teachers in addressing bullying behaviour in schools, with a focus on case studies in several junior high schools and Islamic junior high schools in Jakarta. Bullying behaviour among students is becoming an increasingly worrying issue, given its negative impact on students' psychological and academic development. IR teachers, as educators who play a role in shaping students' character and morality, are expected to play a key role in addressing this issue through an approach based on religious values. The research approach used is qualitative with a case study method. Data was collected through in-depth interviews with IR teachers, participatory observation in the classroom, and analysis of relevant documents. The results of the study show that PAI teachers in junior high schools and MTs in Jakarta implement various strategies to address bullying, including preventive approaches through the teaching of Islamic values, direct intervention with perpetrators and victims of bullying, and collaboration with guidance counsellors and parents. These strategies are also supported by contextual learning that links religious teachings to real-life situations faced by students. However, this study also found a number of challenges faced by PAI teachers, such as limited time in the curriculum, lack of special training related to bullying management, and resistance from students and parents. Therefore, this study recommends the need to strengthen the role of PAI teachers through more intensive training, as well as increased cooperation between schools, parents, and the community to create a more conducive environment for bullying prevention.